2022
DOI: 10.1039/d2nj04693h
|View full text |Cite
|
Sign up to set email alerts
|

Mixed-halide copper-based perovskite R2Cu(Cl/Br)4 with different organic cations for reversible thermochromism

Abstract: Two-dimensional (2D) hybrid perovskites have shown multifeatures owing to their multiple quantum wells structure. Here, we show the synthesis and characterization of 2D mixed-halide Cu-based perovskite crystals, R2Cu(Cl/Br)4, with three...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Generally, the inorganic network is viewed as the major contribution to most properties of materials, while various organic cations could result in completely different properties as well . It was demonstrated that designing an organic cation is an effective way to endow the 2D perovskites with different properties. , So far, various single-cation copper-based perovskites (such as methyl, butyl, and hexyl ammonium cations) with different chemical compositions (e.g., ratios of halogen elements) and crystal structures (monoclinic, orthorhombic, hexagonal, etc. ) , have been reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Generally, the inorganic network is viewed as the major contribution to most properties of materials, while various organic cations could result in completely different properties as well . It was demonstrated that designing an organic cation is an effective way to endow the 2D perovskites with different properties. , So far, various single-cation copper-based perovskites (such as methyl, butyl, and hexyl ammonium cations) with different chemical compositions (e.g., ratios of halogen elements) and crystal structures (monoclinic, orthorhombic, hexagonal, etc. ) , have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…16 It was demonstrated that designing an organic cation is an effective way to endow the 2D perovskites with different properties. 5,17 So far, various single-cation copper-based perovskites (such as methyl, butyl, and hexyl ammonium cations) 18 with different chemical compositions (e.g., ratios of halogen elements) 19 and crystal structures (monoclinic, orthorhombic, hexagonal, etc.) 13,20 have been reported.…”
Section: ■ Introductionmentioning
confidence: 99%